Ekspresi Transforming Growth Factor-beta dan Growth Differentiation Factor-9 Oosit Domba yang Divitrifikasi Sesudah dan Sebelum Maturasi In Vitro - Faizah, Zakiyatul; Aswin, Raden Haryanto (Jurnal Veteriner, 2021)
Oocyte vitrification today became a hope to preserve fertility. Its was a major challenge because of oocyte  characteristic in every phase. Immature oocytes were more sensitive to osmotic stress and the membrane wes less stable while mature oocyte have spindles that were very susceptible to temperature decrease. The study aim  to compare the effect of vitrification before and after in vitro maturation to the expression TGF beta and GDF9. Oocyte of ewes divided into control groups (K0), K1 maturation prior vitrification, K2 vitrification prior maturation. Vitrification begins with washing oocytes  in PBS supplemented of  20%serum for 1-2 minutes, followed by equilibration medium PBS + 20% serum + 10% ethylene glycol for 10-14 minutes,  then transferred to 20% serum + PBS + 0.5 M sucrose + 15% ethylene glycol + PROH 15% for 25-30 seconds. Thawing was processed by in the media: 1). PBS + 20% serum + 0.5 M sucrose, 2).PBS + 20% serum + 0.25 M sucrose, and 3).PBS + 20% serum + 0.1 M sucrose. Immunocytochemical stain was performed to evaluate TGF ? and GDF9 expression. Remmele scale index (IRS) was used to read the result. TGF beta expression both in oocyte and cummulus of K0 and K1 was  significant statistically difference (p<0.05) compare with K2. GDF9 expression both in oocyte and cummulus of K0 and K1 was  significant statistically difference (p<0.05) compare with K2. We concluded that immature oocyte give better expression of TGF â and GDF9 than mature oocyte.